Common mental disorders and barriers to adherence to HIV medications among emerging adults living with HIV using healthcare services in Harare - Saruchera, Emily Wendy (Department of Psychiatry and Mental Health, 2021)
Background: Emerging adulthood (18 to 29 years old) is a critical age group in relation to the Human Immunodeficiency Virus (HIV) epidemic and to mental health. A major public health concern globally, in management of HIV, is that emerging adults have suboptimal antiretroviral therapy (ART) adherence, yet they are the largest group initiating ART. In addition, common mental disorders (CMDs), including depression and anxiety have their peak incidence during this period and they have been found to increase risk of non-adherence to ART. Those with CMDs may have different types of barriers than those without CMDs. Furthermore, those with CMDs might be more likely to have a greater number of barriers to adherence than those without because of the way symptoms of CMDs impact on memory, problem solving skills and concentration. Aims: The main aim of this study was to describe barriers to adherence to ART in emerging adults living with HIV with probable CMDs (i.e. depression and/or anxiety) and accessing HIV treatment at a government clinic in Harare, Zimbabwe, compared to emerging adults living with HIV without probable CMDs. The specific objectives were: a. to determine the prevalence of probable CMDs among emerging adults living with HIV, b. to describe the prevalence, severity and common barriers to ART adherence, measured using the 22-item Barriers to Adherence (BARTA scale) in emerging adults living with HIV with probable CMDs and to compare this with those without probable CMDs. Methods: A representative sample of 223 emerging adults aged 18 to 29 years were recruited in a crosssectional study using the random sampling technique. The Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder-7 (GAD-7) and Barriers to Adherence Scale (BARTA scale) were used to assess probable depression, probable anxiety and barriers to adherence respectively. Data Analysis: Univariate Descriptive statistics were used to describe the socio-demographic, prevalence of probable CMDs, prevalence of barriers to adherence, overall median of total BARTA score (severity of barriers to ART adherence) for the whole sample and overall median number of barriers to ART adherence for the whole sample. Chi-square analyses were used to compare the prevalence of barriers (no barrier vs. at least one) between participants with and without probable CMDs. Non-parametric Wilcoxon rank-sum tests and Kruskal Wallis tests (for variables with more than two categories) were used to I. Compare the number of barriers to ART adherence between participants with and without a probable CMDs; II. Compare the severity of barriers to ART adherence between participants with and without probable CMDs, using overall scores on the BARTA scale III. Assess the relationship between demographic variables, HIV related variables, Substance Use Disorders (SUD) and total BARTA scores. Variables which were significantly associated with BARTA scores were entered into a negative binomial regression model, to assess the relationship between CMDs and severity of barriers to ART adherence, this time controlling for possible demographic confounding factors. Results: The prevalence of probable CMDs (i.e. probable depression and/or probable anxiety) was 33.2%. Specifically, 31.8% had probable depression and 16.1% had probable anxiety. Results: showed that 76.2 % of the sample experienced at least one barrier to ART adherence and that 94.5% of those with CMDs experienced at least one barrier to adherence compared to 67.1% of those without CMDs (p>0.001). We found a significant difference (U=-7.209, p<0.001) between the number of barriers experienced by participants with and without CMDs: participants with a CMD reported a greater number of barriers (median (md) =5, IQR=3-7) compared to those without CMDs (md= 1, IQR=0-4). A statistically significant difference was also found in total BARTA scores between participants with and without CMDs: participants with a CMD reported a greater BARTA score (md=7, IQR=4-12) compared to those without a CMD (md= 2, IQR=0-4; U=-7.415, p<0.001). The most frequent barriers reported by emerging adults living with HIV with probable CMDs were 'forgetting' (68.0%), 'thinking too much' (49.0%), 'having to take ART in front of others' (41.0%) and 'not having a reminder' (39.0%). The most frequent barriers for emerging adults living with HIV without probable CMDs were 'forgetting' (30%), 'not having medications with them' (21%), 'not wanting others to know their status' (20%) and 'not having a reminder' (19%). Although 'forgetting' and 'not having a reminder' were among the top barriers in both groups, those with probable CMDs reported them more frequently. Conclusion: This study has shown that firstly, CMDs and barriers to ART adherence are prevalent among emerging adults living with HIV. Secondly, emerging adults living with HIV with probable CMDs experience a high number of barriers to ART adherence and more severely than those without probable CMDs. Finally, emerging adults with CMDs reported barriers such as forgetting and not having a reminder more frequently than those without CMDs. This calls for routine screening for probable CMDs and barriers to ART adherence in HIV clinics. Furthermore, there is need to come up with tailored psychological interventions that can simultaneously treat CMDs and reduce barriers to ART adherence among emerging adults living with HIV.